PENGARUH MEDIA KOMIK TERHADAP TINGKAT MOTIVASI BELAJAR SISWA KELAS II DI SDN PAKIS VIII SURABAYA - Fitria Anggraeni; Umar Susanto, Rudi; Ghufron, Syamsul; Djazilan, M. Sukron (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was conducted due to the low learning motivation of second-grade students of SDN Pakis VIII Surabaya in Indonesian language learning which is still dominated by conventional methods so that students are less active and easily bored. The research used a quantitative approach with a one-group pretest-posttest design involving 29 students. Data were obtained through a learning motivation questionnaire that had met the validity and reliability tests, then analyzed using the Shapiro-Wilk test, Wilcoxon Signed Rank Test, and N-Gain Score. The results showed that comic media had a significant effect on student learning motivation (p = 0.000 <0.05). The N-Gain value of 0.67 (67%) was in the moderate category, with an increase in the average motivation score from 3.45 to 4.52.